2007
DOI: 10.1007/s00774-006-0735-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of raloxifene and bisphosphonates based on adherence and treatment satisfaction in postmenopausal Asian women

Abstract: We evaluated adherence with raloxifene therapy compared with daily bisphosphonate in Asian postmenopausal women at increased risk of osteoporotic fractures. In this 12-month observational study conducted in Asia (Hong Kong, Malaysia, Pakistan, Philippines, Singapore, Taiwan), 984 postmenopausal women (aged 55 years or older) were treated with raloxifene 60 mg/day (n = 707; 72%) or daily bisphosphonate (alendronate 10 mg/day; n = 206; 21%, or risedronate 5 mg/day; n = 71; 7%) during their normal course of care.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…It is well known that this drug is effective irrespective of race [27][28][29][30][31][32][33]. Therefore, we can predict that the side effects from bisphosphonate are also independent of race.…”
Section: Discussionmentioning
confidence: 79%
“…It is well known that this drug is effective irrespective of race [27][28][29][30][31][32][33]. Therefore, we can predict that the side effects from bisphosphonate are also independent of race.…”
Section: Discussionmentioning
confidence: 79%
“…An observational study comparing raloxifene and bisphosphonates based on adherence and treatment satisfaction in postmenopausal Asian women concluded that osteoporotic women taking raloxifene exhibited lower discontinuation rates and higher treatment satisfaction compared to bisphosphonates [20]. However, this study had several limitations, including the fact that the data were collected through a questionnaire administered to patients.…”
Section: Introductionmentioning
confidence: 97%
“…57,91 In a study 57 of postmenopausal Asian women, the 12-month completion rate for daily treatment with either alendronate or risedronate was significantly lower than that with raloxifene (37.5% vs. 50.2%, p < 0.001). Results of a Spanish study 91 that evaluated daily therapy with raloxifene or alendronate over a 1-year period also showed significantly higher compliance rates in patients receiving raloxifene vs. alendronate (68.7% vs. 54.0%, p < 0.001).…”
Section: Strontium Ranelatementioning
confidence: 81%
“…In both studies, women taking raloxifene reported greater satisfaction with treatment compared with those taking bisphosphonates ( p < 0.01). 57,91 Discontinuation rates for women taking hormone therapy appear to be generally similar to or greater than that for women taking bisphosphonates or raloxifene. 89 Poor persistence with treatment may be associated with smaller decreases in bone turnover, smaller increases in BMD, and a higher risk of fracture and disability.…”
Section: Strontium Ranelatementioning
confidence: 84%
See 1 more Smart Citation